The Paradox of Economic Globalization: The Case of the Niger Delta Region - Obisike, Justina Adalikwu; Obisike, Ebere E. (Mediterranean Journal of Social Sciences, 2012)
Globalization presents contradictions, leading to its manifestation as good and bad â€“ a double edgedsword. For the proponents of globalization, it is a unifying force, an economic process that offers people avariety of choices, leading to an improved quality of life. One can also argue that globalization is goodgiven the example of China and Indian where most people have moved from abject poverty. However, thenegative aspect of globalization has resulted in a tremendous income inequality in most developingnations. There is a high rate of unemployment in these countries as both skilled and unskilled youths havebecome increasingly marginalized and disfranchised from the promise of â€œdevelopment.â€ The position ofthis paper is that, the processes of globalization in the last few decades have continuously restrictedpeopleâ€™s lives, widened the gap between the rich and poor, north and south, resulting in a fragmentedglobality. And for the particular case of the Niger Delta region, economic globalization has resulted in thedisenfranchisement of the youths. The discussions of this socio-economic phenomenon in this paper will bebased on the field work that commenced in 2004 to 2010 in Obagi, Obelle, Omoku, Ogbogu, and Obitecommunities